Increased visceral adiposity index associated with sexual dysfunction in men. (3rd July 2018) - Dursun, Murat; Besiroglu, Huseyin; Cakir, Suleyman Sami; Otunctemur, Alper; Ozbek, Emin
Abstract: Objective: Visceral adipose index (VAI) is a novel parameter for the evaluation of visceral obesity. As we know that obesity is a risk factor for erectile dysfunction (ED). So, in this study, we compared the VAI levels between the men with ED and without ED. Materials and method: A total of 177 men were included in the study. Ninety-five men with ED and 82 men without ED (control). All men were evaluated for ED by Index of Erectile Function-5 items (IIEF-5). VAI levels were calculated using body mass index, high density lipoprotein and tryglyceride levels. Results: Mean age was 53.5 (38–69) in men who have ED and 53.1 (34–69) in control. The men with ED had higher body mass index (BMI), triglyceride (TG) levels, higher waist circumference (WC) and lower high-density lipoprotein-cholesterol (HDL-C) levels. Mean VAI level was 5.18 ± 2.50 in study group and 3.47 ± 1.76 in control goup, respectively. VAI levels were statistically higher in men with ED ( p  < .001). Discussion: The simplicity of WC and BMI measurement and TG and HDL assessment, make VAI an easily applicable index for the evaluation of visceral fat dysfunction. VAI can be useful index for the evaluation and calculation of erectile dysfunction risk.